2022
DOI: 10.1101/2022.12.22.521557
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delineating mouse β-cell identity during lifetime and in diabetes with a single cell atlas

Abstract: Multiple single-cell RNA sequencing (scRNA-seq) datasets have been generated to study pancreatic islet cells during development, homeostasis, and diabetes progression. However, despite the time and resources invested into the past scRNA-seq studies, there is still no consensus on islet cell states and associated pathways in health and dysfunction as well as the value of frequently used preclinical mouse diabetes models. Since these challenges can be only resolved with a joint analysis of multiple datasets, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 228 publications
0
25
0
Order By: Relevance
“…Data for each of the three use cases was prepared separately as described below. For the mouse-human data, we used pancreatic islet datasets of mouse 1 (without embryonic and low-quality cells) and human 58 , for the organoid-tissue scenario we used a retinal dataset 7 , and for the cell-nuclei scenario we used adipose dataset 59 (using the SAT fat type). We obtained published count data and cell annotation for all datasets (see Data availability section) and removed unannotated cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data for each of the three use cases was prepared separately as described below. For the mouse-human data, we used pancreatic islet datasets of mouse 1 (without embryonic and low-quality cells) and human 58 , for the organoid-tissue scenario we used a retinal dataset 7 , and for the cell-nuclei scenario we used adipose dataset 59 (using the SAT fat type). We obtained published count data and cell annotation for all datasets (see Data availability section) and removed unannotated cells.…”
Section: Methodsmentioning
confidence: 99%
“…The joint analysis of multiple single-cell RNA sequencing (scRNA-seq) datasets has recently provided new insights that could not have been obtained from individual datasets. For example, pooling of datasets generated in different studies enabled cross-condition comparisons 1,2 , population-level analysis 3,4 , and revealed evolutionary relationships between individual cell types 5 . The selection of pre-clinical models, such as organoids and animals, and the characterization of their limitations likewise rely on comparison with human tissues [6][7][8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent accumulating evidence in rodents has shown that aged animals and senescent islets tend to express less β-cell transcription factors ( Pdx-1 , Nkx6.1 , FoxO1 , and MafA ) and functionally important genes ( Ins1 , Ins2 , Slc2a2 , and Slc30a8 ), along with more expression of β-cell dedifferentiation markers ( Sox9 and Aldh1a3 ). [38] Similarly, in the human pancreas, PDX1 expression is markedly downregulated with aging. [39] Remarkably, a single-cell RNA-seq analysis revealed that the number of bihormonal cells that simultaneously expressed both insulin and glucagon mRNA increased with age, and the presence of such transcriptionally noisy cells suggests a fate drift between α- and β-cells in the aging pancreas, resulting in a loss of β-cell identity and function.…”
Section: Mechanisms Leading To β-Cell Failurementioning
confidence: 99%
“…STZ is a naturally occurring diabetogenic compound that targets and destroys insulin-secreting pancreatic β cells, leading to reduced insulin levels and elevated blood glucose levels [52][53][54]. In the mSTZinduced diabetic models, STZ is applied in multiple low doses, partially degrading β-cell activity [55], where the level of degradation may differ between individual cells [56]. To quantify the damage to individual cells extracted from mSTZ-induced diabetic models, we evaluate their trainability for a disease label against the backdrop of control cells annotated as healthy.…”
Section: Inference Of Disease-related Cell States and Treatment Respo...mentioning
confidence: 99%